Management of infections with Mycobacterium other than tuberculosis as a complication of surgical procedures - Naskar, Bikash; Bakshi, Sabyasachi; Mandal, Tapas (International Surgery Journal, 2020)
Background: Atypical Mycobacterium other than tuberculosis (MOTT) have emerged as significant human pathogens, causing post-surgical wound infections. The aim of this study is to assess the causative organisms of such infection and their treatment response. Methods: After matching the criteria, 28 cases, were taken for this prospective, single center, observational study. The diagnosis was confirmed by bacterial culture. Results: Among 28 patients, 16 were females (median age of 45.5 year). Patients had undergone laparoscopic cholecystectomy (n=13), laparoscopic appendicectomy (n=3), laparoscopic hernioplasty (n=2), open appendicectomy (n=2), open mesh hernioplasty (n=7), exploratory laparotomy (n=1). No major comorbidities or immunosuppression was identified. All patients were initially treated with repeated incision and drainage and started conventional antibiotics until culture and sensitivity report was available. All except one patient had culture confirmed MOTT infection. Combination antibiotics (clarithromycin, linezolid and ofloxacin) given for initial 3 months. 12 well responded within 3 months. 9 required additional few months to get complete cure. 4 patients cured after 6 months of treatment and 3 patients did not come for follow up. Conclusions: Delayed onset chronic wound infection by atypical mycobacteria is preventable. These organisms are not responsive to conventional antitubercular drugs but to specific drug regimens.